Application of endoscopic hemoclips for nonvariceal upper gastrointestinal bleeding in children - Ünal, Fatih; Çakır, Murat; Baran, Maşallah; Duygulu, Şengül; Aydoğdu, Sema (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Data about the efficiency and outcome of therapeutic endoscopic techniques in children with nonvariceal upper gastrointestinal bleeding (UGB) are scarce. We aimed to analyze our experience with endoscopic hemoclip application in children with non-variceal UGB. Materials and Methods: During a 3-year period, a total of 1715 endoscopies were performed in our pediatric endoscopy unit; 182 (10.6%) of them were performed for UGB to 158 patients. Fifty-six of them had emergent endoscopy. Among them, 15 cases with nonvariceal UGB were only given endoscopic hemoclips. Demographic, clinical, and laboratory findings at initial admission; endoscopic appearance of bleeding lesions; and outcome of hemoclip application were recorded from the hospital files and endoscopy records. Results: Ten patients (66.6%) had gastric ulcer, 3 (20%) had duodenal ulcer, 1 (6.7%) had Dieulafoy lesion, and 1 (6.7%) had bleeding at the post-polypectomy site. Initial homeostasis after hemoclip application was achieved in all patients (100%). Rebleeding was seen in only one patient (6.5%) with a Dieulafoy lesion, who needed hemoclip application for a second time, and the bleeding was controlled successfully. Permanent hemostasis was 100%. The median number of hemoclips used per case and per application was 3.4 and 3.2, respectively. None of the patients experienced any complication related to hemoclip application. Median duration of hospitalization was 6 days. On follow-up, none of the patients received surgical therapy, and 30-d mortality related to bleeding was 0%. Conclusion: The use of hemoclips for nonvariceal UGB in children is an effective modality to control bleeding without any complications in children.